Growing labor productivity and securitization – the two surprising factors of income inequality - Sopoćko, Andrzej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The paper tries to indicate two reasons for worldwide growing income disparity. The first one is capitalism transformation from individual ownership to anonymous, broadly diversified portfolio holders, who do not adhere to a particular company for a long time. The leading role is played by the company management, especially its CEO. Capital owners become finance holders who look only at temporarily best investment opportunities. Therefore, the managers are compelled to race for higher rate of return. To ensure that the assets portfolio of financial owners is diversified, financial capitalists prefer short-time investment strategies, focusing more on short-time efficiency than on long-time development, mainly on cost reductions, including workers’ salaries. Such efforts are accompanied by a strong and continuous rise in labour productivity (the second factor). Over time, fewer people are needed to participate in the production process, which contributes to the weakness of the labour force in the struggles for salary. This constrains the income rise for a big part of the society and leads to a global demand squeeze
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 240-251
Keywords: LTRO; money supply; income distribution; podaż pieniądza; podział dochodów